2021
DOI: 10.3390/jcm10020286
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Distribution Width, Disease Severity, and Mortality in Hospitalized Patients with SARS-CoV-2 Infection: A Systematic Review and Meta-Analysis

Abstract: The identification of biomarkers predicting disease severity and outcomes is the focus of intense research in patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2 infection). Ideally, such biomarkers should be easily derivable from routine tests. We conducted a systematic review and meta-analysis of the predictive role of the red blood cell distribution width (RDW), a routine hematological test, in patients with SARS-CoV-2 infection. We searched the electronic databases PubMed, Web of Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 50 publications
1
17
1
2
Order By: Relevance
“…(19) Table 4 shows significant increase in RDW-SD, RDW-CV and decrease in MCVin patients with severity of disease, which is similar to the study done by Wang et al (18). Also, Zinellu & Mangoni et al (20) found that the severely ill COVID-19 patients had significantly elevated RDW in comparison to the patients without severity which is also consistent with our study, that the elevated RDW is associated with disease severity.…”
Section: Red Blood Cell Morphology In Covid;supporting
confidence: 91%
“…(19) Table 4 shows significant increase in RDW-SD, RDW-CV and decrease in MCVin patients with severity of disease, which is similar to the study done by Wang et al (18). Also, Zinellu & Mangoni et al (20) found that the severely ill COVID-19 patients had significantly elevated RDW in comparison to the patients without severity which is also consistent with our study, that the elevated RDW is associated with disease severity.…”
Section: Red Blood Cell Morphology In Covid;supporting
confidence: 91%
“…A number of studies have reinforced this evidence, like showed in a meta-analysis carried out in Australia. The RDW values were significantly higher in patients with COVID-19 considered severe (severe clinical manifestations and/or intensive care support or even death), when compared with the patients that showed mild symptoms (Zinellu & Mangoni, 2021).…”
Section: Rdw and Covid-19mentioning
confidence: 82%
“…Mortality risk in Covid-19 seems to be associated with higher erythrocyte distribution width (RDW), a measure of heterogeneity of erythrocyte volume (Figure 2). In a meta-analysis of Covid-19 patients, higher RDW was associated with more severe disease [38]. The precise reason for this is unknown, but may involve reduced erythropoiesis or impaired erythrocyte clearance.…”
Section: The Erythrocyte and Virusmentioning
confidence: 99%